2018
DOI: 10.1111/pan.13329
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of intravenous acetaminophen and ketorolac in adolescents undergoing idiopathic scoliosis surgery

Abstract: Intravenous acetaminophen with or without ketorolac reduced opioid consumption, opioid-related adverse effects, length of stay, and thereby cost of care following idiopathic scoliosis in adolescents compared with opioids-alone postoperative analgesia strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The lack of differences in opioid use at these points of the perioperative pathway is likely due to providers giving standard doses on induction of anesthesia, as well as throughout the case, and reflex prescribing when a patient requests an analgesic or reports an elevated pain score to the PACU providers. This is a point of needed improvement in our ERAS protocol, and we encourage others developing perioperative analgesic protocols to consider an algorithm for addressing pain in the PACU and whether or not they will give recommendations for intraoperative analgesic administration 13‐16 …”
Section: Discussionmentioning
confidence: 99%
“…The lack of differences in opioid use at these points of the perioperative pathway is likely due to providers giving standard doses on induction of anesthesia, as well as throughout the case, and reflex prescribing when a patient requests an analgesic or reports an elevated pain score to the PACU providers. This is a point of needed improvement in our ERAS protocol, and we encourage others developing perioperative analgesic protocols to consider an algorithm for addressing pain in the PACU and whether or not they will give recommendations for intraoperative analgesic administration 13‐16 …”
Section: Discussionmentioning
confidence: 99%
“…LOS after PAO was shown in prior studies to be 4–5 days [ 24 ], similar to what we found in the EP protocol (4.38 ± 1.02 days). In our previous studies investigating the cost-effectiveness of analgesic regimens after spine fusion, we found that average daily in-patient costs in an orthopedic ward ≈ $2654 (direct costs≈$1639; indirect costs≈$1015) [ 25 ]. Thus, MM-FICNB protocol, associated with significantly decreased length of stay (2.88 ± 0.72 days) has the potential to significantly improve value-based care, decreasing cost without affecting analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of paracetamol to an NSAID in our study was associated with faster oral fluid tolerance, particularly in patients given morphine-PCA. Faster oral intake with the combination of acetaminophen–ketorolac–opioids over opioids alone and opioids–acetaminophen was recently reported in an observational study of adolescents after scoliosis surgery [26]. However, no comparison was provided with the opioids–ketorolac group.…”
Section: Discussionmentioning
confidence: 99%